MOTIVASI WARGA BELAJAR MENGIKUTI PROGRAM PAKET B DI PKBM PELITA RIAU JALAN BALAI PERNIKAHAN KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Rana Mutia; Wilson '; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the condition of learners in CLC Pelita Riau Pekanbaru City. The research problem was whether the motivation that encourages learners followed the Package B Program in CLC Pelita Riau Pekanbaru City?. The purpose of this research was to determine the motivation that encourages learners followed the Package B Program in CLC Pelita Riau Pekanbaru City. The population in this research as many as 30 people learners the program package B in PKBM Pelita Riau, then the sample of this research was 30 people and 20 people sample trial. The sample used was a saturated sample. The data completion instrument was a questionnaire with 67 statements and after the trial live 60 valid statements to be used as research instruments. Data Analysis through Quantitative Descriptive analysis. From the calculation of the percentage of answers findings research motivation Learners Followed the Package B Program in CLC Pelita Riau Pekanbaru City is extrinsic motivation with percentage value (SB + B) 77.74% This means that external motivation has a high influence on the learners Following Program package B in CLC Pelita Riau Pekanbaru City.Keywords: Motivation, Student Learning, Package B Program,CLC Pelita Riau